Scattering of Radiation by a Periodic Structure of Circular and Elliptical Microcavities in a Multimode Optical Waveguide - Alexandra Yu. Petukhova; Anatolii V. Perminov; Mikhail A. Naparin; Victor V. Krishtop (Photonics)
We developed a mathematical model to examine the scattering of radiation by a periodic structure of circular and elliptical microcavities formed in a planar optical waveguide. The waveguide simulates the behaviour of a 62.5/125 µm multimode optical fibre. The calculations focused on the intensity distribution of scattered light with a wavelength of 1310 nm along the periodic structure, i.e., along the side surface of the waveguide, as a function of the microcavity dimensions and their spatial arrangement within the waveguide core. The optimal geometrical parameters of the microstructure, ensuring the most uniform light scattering, were identified. The model is valid for multimode optical fibres containing strictly periodic structures of microcavities with spherical or elliptical cross-sections that scatter laser radiation in all directions. One potential application of such fibres is as light sources in medical probes for surgical procedures requiring additional illumination and uniform irradiation of affected tissues. Furthermore, the findings of this study offer significant potential for the development of sensing elements for fibre-optic sensors. The findings of this study will facilitate the design of scattering structures with microcavities that ensure a highly uniform scattering pattern.